Phenomenological Features of Concentration - A.V. Melnikov; M.G. Yusupov (Ученые записки Казанского университета: Серия Гуманитарные науки)
Concentration is of great importance for optimization of cognition and practical activities of a person, especially in the course of learning and creative activity. Investigation of students’ concentration allows to expand the ideas of activity, as well as to plan ways of organization and regulation of students’ training. The purpose of this research is detection of the psychological and physiological features in students as they concentrate; in order to reveal the intensity of psychological and physiological manifestations of this state influencing the success of problem solving, frequency analysis is performed. A total of 150 students of the first, second, and third courses at the average age of 19 years participated in the research. Respondents were asked to complete a specially developed questionnaire, answer questions, and describe the characteristic psychological and physiological features exhibited during the process of concentration. On the basis of the obtained results, the following conclusions were drawn. The state of concentration is typical for various educational situations: solution of difficult tasks, sitting of examinations, passing and failing of examinations. It most often arises in the situations of tests. Concentration is endured as a positive condition and has a good influence on the overall success of training. The duration of this state varies from 20 to 120 minutes and the intensity may be from 7 to 8 points depending on the type of tasks (on the 10-point scale). The condition of concentration is characterized by the following main implications: in the cognitive sphere – highly focused thinking, fixation on the object of cognition, depression of speech activity; in the somatic sphere – sweating of hands, tremor of fingers, stiffness of body muscles, heart acceleration, retardation of motility, and deep breathing. The factors interfering with the manifestation of concentration are lack of motivation for training, physical health, distracting factors (such as noise), poor initiative, forgetfulness, and emotional sufferings.